Designing for control : Embedded Digital Interventions to Counter Compulsive Short-Form Video Use - Lafitte, Ewald (My University, 2025)
Short-form video (SFV) platforms like TikTok have become dominant in the digital media landscape, driven by immersive design features such as algorithmic personalization, continuous scroll, and high sensory stimulation. While these features maximize engagement, growing evidence links SFV use to compulsive behavior, impaired attention, and weakened self-regulation. Traditional awareness tools—such as screen time apps—often fail in such environments, as they rely on voluntary self-control despite the platform’s intent to suppress it. This thesis investigates whether embedded digital interventions, implemented directly within the consumption flow, can counteract compulsive SFV usage. A between-subjects experiment was conducted using a custom-built SFV platform, testing and comparing two conditions: a friction-based timer and a targeted motivational warning. The study measured behavioral outcomes, perceived control, and future intervention acceptance. Findings show that both intervention types significantly reduced perceived overconsumption and increased user reflection. Tailored warnings were also rated as more supportive, though behavioral outcomes were similar across types. These results suggest that embedded interventions can help restore user agency in digital environments explicitly designed to undermine it, offering practical insights for platform designers and policymakers.
Keywords: Short-form video, Digital interventions, Interface design, Compulsive media use, Behavioral nudges, Friction awareness, Digital well-being